1999
DOI: 10.1046/j.1524-4725.1999.99108.x
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Pulsed Light Source Hair Removal Device Used to Evaluate the Onset of Action of a New Topical Anesthetic

Abstract: ELA-Max is an effective topical anesthetic agent comparable to EMLA under occlusion. It appears to be faster acting than EMLA, and along with its effectiveness without occlusion, may be an easier agent to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Although EMLA cream and lidocaine HCl are both used as local anesthetics, lidocaine has demonstrated a more rapid onset and a longer duration compared with EMLA cream. 16 Regarding study design, the study of Borckardt et al 15 was limited, as it enrolled only healthy subjects (eg, patients with a medical or psychiatric diagnosis were not included), used EMLA cream in 2 participants, and had few rTMS sessions that were brief. The clinical application of rTMS for the treatment of depression will most likely involve a longer treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…Although EMLA cream and lidocaine HCl are both used as local anesthetics, lidocaine has demonstrated a more rapid onset and a longer duration compared with EMLA cream. 16 Regarding study design, the study of Borckardt et al 15 was limited, as it enrolled only healthy subjects (eg, patients with a medical or psychiatric diagnosis were not included), used EMLA cream in 2 participants, and had few rTMS sessions that were brief. The clinical application of rTMS for the treatment of depression will most likely involve a longer treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, ELA-Max has been shown to produce less vasoconstriction and result in a lower serum lidocaine level. 9,10 Package labeling for ELA-Max does not state that an occlusive dressing should be used. To help keep the cream in place, we chose to use a Tegaderm occlusive dressing.…”
Section: Discussionmentioning
confidence: 99%
“…Another local anesthetic cream with a shorter onset of action (~30 min), ELA-Max, is also available and is composed of 4% liposomal lidocaine [ 71 ] . One study by Eichenfi eld and others observed comparable effi cacy between ELA-Max at 30 min and EMLA cream applied 60 min before the procedure [ 72 ] .…”
Section: Topical Analgesiamentioning
confidence: 99%